2014
DOI: 10.1371/journal.pone.0101505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Characterization and Health Burden of Thalassemia in Jiangxi Province, P. R. China

Abstract: BackgroundThalassemia is the most common inherited disease in southern China. However, this disorder is usually ignored by Jiangxi provincial health system and government due to lack of epidemiological data.Materials and MethodsA total of 9489 samples from Hakka Han and Gan-speaking Han in three geographical areas of Jiangxi Province were analyzed for both complete blood cell (CBC) count and reverse dot blot (RDB) gene chip for thalassemia.Results1182 cases of suspected thalassemia carriers with microcytosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
47
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 19 publications
16
47
7
Order By: Relevance
“…However, no epidemiological study of thalassemia has been reported for Sichuan Province. First, we found a relatively lower genetic frequency of thalassemia (3.43%, 112/3262) in the Chengdu region compared with most regions of Southern China, including Guangxi (24.51%, 172/1182, p50.05), Guangdong (11.07%, 478/5605 + 198/7792, p50.05) and Southern Jiangxi (9.49%, 1419/5789, p50.05) (14)(15)(16). In the population studied here, 2.21% cases carried a-thal mutations; a-thal is mainly caused by the Southeast Asian deletion (--SEA ), which displays normal Hb values or slightly hypochromic anemia.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, no epidemiological study of thalassemia has been reported for Sichuan Province. First, we found a relatively lower genetic frequency of thalassemia (3.43%, 112/3262) in the Chengdu region compared with most regions of Southern China, including Guangxi (24.51%, 172/1182, p50.05), Guangdong (11.07%, 478/5605 + 198/7792, p50.05) and Southern Jiangxi (9.49%, 1419/5789, p50.05) (14)(15)(16). In the population studied here, 2.21% cases carried a-thal mutations; a-thal is mainly caused by the Southeast Asian deletion (--SEA ), which displays normal Hb values or slightly hypochromic anemia.…”
Section: Discussionmentioning
confidence: 77%
“…Hainan and Southern Jiangxi provinces (10)(11)(12)(13)(14). To propose effective public health strategies for the prevention and control of thalassemia, it is important to first obtain reliable epidemiological data for the local population.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were probably caused by different genetic screening methods and/or population mobility and migration. The rate of thalassemia in Chenzhou was significantly higher than the average of Hunan Province (4.18%) and was closer to that of Guangdong Province and southern Jiangxi Province . Notably, the rates of α and β‐thalassemia in Chenzhou had a special distribution pattern.…”
Section: Discussionmentioning
confidence: 84%
“…It has been shown that the carrier rate of alpha-thalassemia is much higher than in Nanchang (1.49%) and Xinyu (2.2%) and slightly lower than in Ganzhou (7.19%) in Jiangxi [13]. The carrier rate of betathalassemia is higher than in Nanchang (1.14%), Xinyu (1.7%) and also slightly lower than Ganzhou (2.3%) [13]. In addition, the composite carrier rates of alpha-thalassemia and beta-thalassemia in…”
Section: Geographical Distribution Of Thalassemia Carriers In Ji'anmentioning
confidence: 96%
“…In recent years, a large-scale investigation of thalassemia was carried out in different regions of China [4,8,12], but the epidemiologic characteristics of thalassemia among people from Jiangxi Province, as one of the high-prevalence areas, especially those from Ji'an City, are not fully understood [13]. Ji'an is located in the central part of Jiangxi Province, with a total area of 25,300 square kilometers and a population of 4,956,600.…”
Section: Introductionmentioning
confidence: 99%